2016
DOI: 10.1021/jacs.6b07014
|View full text |Cite
|
Sign up to set email alerts
|

Through-Space Charge Interaction Substituent Effects in Molecular Catalysis Leading to the Design of the Most Efficient Catalyst of CO2-to-CO Electrochemical Conversion

Abstract: The starting point of this study of through-space substituent effects on the catalysis of the electrochemical CO-to-CO conversion by iron(0) tetraphenylporphyrins is the linear free energy correlation between through-structure electronic effects and the iron(I/0) standard potential that we established separately. The introduction of four positively charged trimethylanilinium groups at the para positions of the tetraphenylporphyrin (TPP) phenyls results in an important positive deviation from the correlation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
799
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(830 citation statements)
references
References 16 publications
29
799
2
Order By: Relevance
“…[5] In biological systems,many catalytic active centers of metalloenzymes are dinuclear metallic complexes, [6,7] such as heterometallic [NiFe 4 (OH)S 4 ]c luster-based carbon mon-oxide dehydrogenase (CODHs), dinuclear-Fe II -based hydrogenase,d inuclear-Cu II -based tyrosinase and laccase,d inuclear-Zn II -based alkaline phosphatase,d inuclear-Cu-Zn bovine superoxide dismutase.B ye xploiting metal-metal cooperativity to accomplish different substrate recognition and transformation, these metalloenzymes undertake diverse physiologic functions in life system. [15][16][17] Thes olar-driven reduction of CO 2 into chemical fuels/ feedstocks represents ap otential strategy for solving the issues of energy crisis and global warming caused by increasing CO 2 emission. [8][9][10][11][12][13][14] In addition, it has been found that the addition of Lewis acidic metal cations to the mononuclear metal electrocatalysts can lower the overpotentials and subsequently increase the activities for the electrocatalytic CO 2 reduction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In biological systems,many catalytic active centers of metalloenzymes are dinuclear metallic complexes, [6,7] such as heterometallic [NiFe 4 (OH)S 4 ]c luster-based carbon mon-oxide dehydrogenase (CODHs), dinuclear-Fe II -based hydrogenase,d inuclear-Cu II -based tyrosinase and laccase,d inuclear-Zn II -based alkaline phosphatase,d inuclear-Cu-Zn bovine superoxide dismutase.B ye xploiting metal-metal cooperativity to accomplish different substrate recognition and transformation, these metalloenzymes undertake diverse physiologic functions in life system. [15][16][17] Thes olar-driven reduction of CO 2 into chemical fuels/ feedstocks represents ap otential strategy for solving the issues of energy crisis and global warming caused by increasing CO 2 emission. [8][9][10][11][12][13][14] In addition, it has been found that the addition of Lewis acidic metal cations to the mononuclear metal electrocatalysts can lower the overpotentials and subsequently increase the activities for the electrocatalytic CO 2 reduction.…”
mentioning
confidence: 99%
“…Ther esults show that one single photoredox cycle produces 8.10 mmol of CO and 0.16 mmol of H 2 within 10 h ( Table 1, Entry 1; Figure 2a), along with trace amount of formate detected in the liquid phase by ion chromatograph (IC). [18] Moreover,w hen the [15][16][17] the experiments of photocatalytic CO 2 reduction by CoCo and Co in the presence of Zn II were performed. This TONvalue is 4-, 19-, and 45-fold higher than those of CoCo (17 000), ZnZn (3400), and Co (1500) under the same conditions (Table 1, entry 2-4; Figure 2b).…”
mentioning
confidence: 99%
“…34 Other work has focused on incorporating proton sources directly into the ligand framework. 33,35 Previously, we have shown that the use of hydrogen-bonding motifs and amino acid residues can switch the dominant catalytic pathway for CO 2 reduction from a unimolecular one to a bimolecular one. 36 This change lowers the observed catalytic potential by ~250 mV.…”
Section: Introductionmentioning
confidence: 99%
“…400 cm 2 membrane in as ingle process) is reported. [6][7][8][9][10][11][12][13][14][15] However,these traditional Notably, CO with 94 %F aradaic efficiency and À103 mA cm À2 current density are readily achieved with only about 1.2 mg catalyst loading, which are among the best results ever obtained by metal-free CO 2 RR catalysts.O nt he basis of control experiments and DFT calculations,s uch outstanding CO Faradaic efficiency can be attributed to the co-doped pyridinic Na nd carbon-bonded Sa toms,w hiche ffectively decrease the Gibbs free energy of key *COOH intermediate.F urthermore,h ierarchically porous structures of NSHCF membranes impart am uchh igher density of accessible active sites for CO 2 RR, leading to the ultra-high current density.…”
mentioning
confidence: 99%
“…This is because CO 2 reduction can be readily conducted in aqueous solution, electrically driven from renewable energy sources,a nd produce value-added fuels or chemicals. [6][7][8][9][10][11][12][13][14][15] However,these traditional [4,5] Thep ast decades have witnessed metals (such as Ag, [6] Pd, [7] Au, [8] Co [9] )a nd their derivatives (that is,m etal oxides and metal complexes) as the most commonly used electrocatalysts for efficient CO 2 RR.…”
mentioning
confidence: 99%